Rachunkowość sektora finansów publicznych na tle rachunkowości sektora prywatnego - Ignor, Marek (Public Finance Sector Accounting Vis a-Vis Private Sector Accounting, 2007)
This article presents specific features of public sector accounting system vis-à-vis private sector accounting system. The analysis of the approach applied in public sector accounting indicates it is necessary to transform the applied principles in order to optimise them from the management processes point of view.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 194-203